MBCL-09. SALVAGE THERAPY FOR CHILDHOOD MEDULLOBLASTOMA: A SINGLE CENTER EXPERIENCE. Issue 2 (22nd June 2018) - Kameda-Smith, Michelle; Wang, Alick; Abdulhadi, Noora; Adile, Ashley; Ajani, Olufemi; Yarascavitch, Blake; Farrokhyar, Forough; Tina, Petrelli; Samaan, Constantine; Alyman, Cheryl; Singh, Sheila; Fleming, Adam
Abstract: INTRODUCTION: Children diagnosed with medulloblastoma (MB) that are refractory to upfront therapy or experience recurrence have very poor prognoses. Reports of phase I and II studies for these children exist, but these therapies bear significant treatment related morbidity and mortality. METHODS: A retrospective review of children diagnosed with a pediatric MB from 2002-2015 from the McMaster Pediatric Brain Tumour Study Group (PBTSG) captured a number of pediatric recurrent MB. RESULTS: Over the 13-year period, 31 children with a histological diagnosis of MB were treated. Thirteen children had recurrent or treatment refractory MB. The 2-year event-free survival (EFS) and overall survival (OS) of our cohort was 67.7% and 80.6% respectively. The mean time to recurrence was 14.6 months. The mean follow-up for survivors of recurrent MB was 4.0 years. Ten patients recurred with disseminated leptomeningeal spread and 3 patients experienced local recurrence. In 3 of the 13 recurrent MB, the disease had significantly progressed and the patients were palliated. For the remaining children, therapy offered included surgery, radiation (CSI or CyberKnife), carboplatin, cisplatin, cyclophosphamide, etoposide, imatinib, irinotecan, methotrexate, temsirolimus, temozolamide, tipifarnib, vinblastine, and vincristine either in isolation or in varying combinations. CONCLUSION: Recurrent MB in our single centre cohort carried a poor prognosis despite administration of salvage therapy. Though there is standardization of the upfront treatment for these children, we observed great heterogeneity in the treatment of our 13 patients experiencing recurrence. A greater understanding of the biology of recurrent MB has the potential to guide salvage therapy.